Influence of age on voice quality after transoral CO2 laser microsurgery - Jerome R. Lechien; Stephane Hans; Lise Crevier-Buchman (Journal of Otolaryngology - Head and Neck Surgery, 2023)
Abstract Objective To study the post-operative evolution of voice quality of patients treated by transoral CO2 laser microsurgery (TLM) according to the age. Methods Patients treated by type I to VI TLM and post-operative speech therapy were prospectively recruited from our hospital. The voice quality was assessed pre-, 1-, 3- 6- and 12-month posttreatment with voice handicap index (VHI), dysphonia, roughness, breathiness, asthenia, strain (GRBAS), maximal phonation time (MPT), F0, F0 standard deviation (STD), percent jitter, percent shimmer, noise-to-harmonic ratio (NHR), vocal fold vibration assessment and speech fluency. Evolution of voice outcomes was analyzed considering age of patients (< 60 vs. ≥ 60 years). Results Seventy-five patients completed the evaluations. Thirty-four and forty-one patients were < 60 or ≥ 60 yo, respectively. Subjective and objective voice parameters (VHI, G, R, B), jitter and fluency significantly improved from 1- to 6-month post-TLM in < 60 yo individuals. The voice parameters improved 12-month post-TLM in the ≥ 60 yo group at the exception of VHI that improved 3-month post-TLM. There were positive associations between age and 12-month NHR, G and A parameters. Conclusion The post-operative evolution of voice quality parameters may vary between patients according to the age. Preoperative VHI is predictive of 12-month subjective and objective voice outcomes. Graphical abstract